2022
DOI: 10.1371/journal.pgph.0000215
|View full text |Cite
|
Sign up to set email alerts
|

Community engaged tick surveillance and tickMAP as a public health tool to track the emergence of ticks and tick-borne diseases in New York

Abstract: A community engaged passive surveillance program was utilized to acquire ticks and associated information throughout New York state. Ticks were speciated and screened for several tick-borne pathogens. Of these ticks, only I. scapularis was commonly infected with pathogens of human relevance, including B. burgdorferi, B. miyamotoi, A. phagocytophilum, B. microti, and Powassan virus. In addition, the geographic and temporal distribution of tick species and pathogens was determined. This enabled the construction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Statistical significance could not be determined for D. variabilis . This is due to the remarkably low rate of D. variabilis nymph/larvae submission, as noted previously 1 . In addition, Dermacentor variabilis is almost exclusively encountered by humans in its adult life stage, with nymphs and larvae are rarely observed on either humans or domestic animals.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…Statistical significance could not be determined for D. variabilis . This is due to the remarkably low rate of D. variabilis nymph/larvae submission, as noted previously 1 . In addition, Dermacentor variabilis is almost exclusively encountered by humans in its adult life stage, with nymphs and larvae are rarely observed on either humans or domestic animals.…”
Section: Resultsmentioning
confidence: 62%
“…For example, in Korea, H. longicornis was determined to prefer abdomen and lower extremities (33%) and the abdomen/inguinal area (26.4%) 21 , which is a behavior similar to that of A. americanum observed here. Although H. longicornis is present in New York 1 , insufficient numbers were detected to draw definitive conclusions about its biting preference here. Additionally, a study in England ( I. ricinus ) reported that tick bites were most common in the legs (50%) of adult humans, but in the head and necks of children (43%) 22 , a differentiation that our survey does not at this time include.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations